2003
DOI: 10.1108/09600030310503334
|View full text |Cite
|
Sign up to set email alerts
|

Developing a framework for evaluating the logistics costs in global sourcing processes

Abstract: Global sourcing is becoming a prerequisite for companies competing in today's market. The logistics costs often comprise a large portion of the total global sourcing cost, thereby determining the effectiveness of this procurement strategy. However, evaluating the logistics cost in a global context is frequently difficult. This paper presents a five‐step evaluation framework and illustrates how this framework can be implemented using a case study at a leading firm in the US aviation industry and its part suppli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 8 publications
1
80
0
3
Order By: Relevance
“…The attention is on mutual understanding and relationships (Enderwick, 2009;Merminod & Rowe, 2012;Lo & Chung, 2007). High levels of trust can be generated by extensive collaboration between all parties involved (Zeng & Rossetti, 2003;Gonzalez et al, 2006;Feenstra &Hanson, 2005, andChen et al (2010, p. 240) point out that a good relationship encompasses teambuilding activities that help establishing "a good interpersonal relationship with providers and [enable] further interpersonal exchanges of knowledge".…”
Section: Dealing With Problems Encountered When Sourcing From Chinamentioning
confidence: 99%
“…The attention is on mutual understanding and relationships (Enderwick, 2009;Merminod & Rowe, 2012;Lo & Chung, 2007). High levels of trust can be generated by extensive collaboration between all parties involved (Zeng & Rossetti, 2003;Gonzalez et al, 2006;Feenstra &Hanson, 2005, andChen et al (2010, p. 240) point out that a good relationship encompasses teambuilding activities that help establishing "a good interpersonal relationship with providers and [enable] further interpersonal exchanges of knowledge".…”
Section: Dealing With Problems Encountered When Sourcing From Chinamentioning
confidence: 99%
“…D. M. Lambent argues that logistics costs can be divided into five categories, purchasing costs, warehouse occupancy costs, storage costs, order processing costs and transportation costs [3]. Christian Rossetti proposed a new classification method applicable to the global inter enterprise logistics system, based on the logistics cost method of Ellram classification [4]. Oud Manunen found that in the investigation of manufacturing enterprises and retail enterprises, logistics operations can be divided into seven types of cost [5].…”
Section: Application and Development Of System Dynamics In Logistics mentioning
confidence: 99%
“…An important part of the context is the culture of the sender and receiver (Steenhuis and de Bruijn, 2007); different cultural settings can affect many aspects of a project, since culture follows people (Zeng and Rossetti, 2003;Fraering and Prasad, 1999;Fawcett and Birou, 1992;Levy, 1995;Johansen et al, 2005). Hofstede and Hofstede (2005) define culture as "the collective programming of the mind that distinguishes the members of one category of people from another".…”
Section: Contextual Differencesmentioning
confidence: 99%
“…There are several frameworks that describe how to carry out an outsourcing process, from initiation to conclusion (e.g., Fredriksson and Johansson, 2009;Franceschini et al, 2003;McIvor, 2000;Momme and Hvolby, 2002;Zeng, 2003).…”
Section: Related Offset Businessmentioning
confidence: 99%